"Competence approach of english teaching language in Ngabe Bugle ethnicity to students of 6th grade in Quebrada de Hacha Elementary Schoo, San Lorenzo District, 2013" - Gutiérrez, Dina; Moreno, Gladis (David, Panamá : UDELAS, 2013)
This approach allows students to develop all their skills in an acative way, in the city and in the indigenous area where was developed this reseach project.
GENERAL INDEX CHART INDEX GRAPHIC INDEX INTRODUCTION CHAPTER I. RESEARCH OF THE PROBLEM CHAPTER II. THEORETICAL FRAMEWORK 2. Competence approach 2.1. Characteristics of competence approach 2.2. Methods used in competence approach 2.2.1. Deductive method 2.2.2. Inductive method 2.2.3. Analog or comparative method 2.2.4. Active method 2.2.5. Audiolingual method 2.2.6. Total physical response 2.2.7. Direct method 2.3. Strategies used in competence approach 2.4. Techniques used in competences approach CHAPTER III. METHODOLOGICAL FRAMEWORK CHAPTER IV. ANALYSIS AND INTERPRETATION OF RESULTS CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY ANNEXES
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA EN INGLÉS; QUEBRADA DE HACHA ELEMENTARY SCHOOL - SAN LORENZO - CHIRIQUÍ